PERAN HUKUM ADMINISTRASI NEGARA DALAM MENGATASI KONFLIK AGRARIA DI INDONESIA - Raihan Brilliawan (PT. Habe Cendekia Utama, 2025)
Agrarian conflicts in Indonesia are complex issues involving various legal, social, and economic aspects. This study, entitled